Common mechanisms explain nitrogen‐dependent growth of Arctic shrubs over three decades despite heterogeneous trends and declines in soil nitrogen availability. Issue 2 (23rd July 2021) - Martin, Andrew C.; Macias‐Fauria, Marc; Bonsall, Michael B.; Forbes, Bruce C.; Zetterberg, Pentti; Jeffers, Elizabeth S.
Summary: Heterogeneity has been observed in the responses of Arctic shrubs to climate variability over recent decades, which may reflect landscape‐scale variability in belowground resources. At a northern fringe of tall shrub expansion (Yuribei, Yamal Peninsula, Russia), we sought to determine the mechanisms relating nitrogen (N) limitation to shrub growth over decadal time. We analysed the ratio of 15 N to 14 N isotopes in wood rings of 10 Salix lanata individuals (399 measurements) to reconstruct annual point‐based bioavailable N between 1980 and 2013. We applied a model‐fitting/model‐selection approach with a suite of competing ecological models to assess the most‐likely mechanisms that explain each shrub's individual time‐series. Shrub δ 15 N time‐series indicated declining (seven shrubs), increasing (two shrubs) and no trend (one shrub) in N availability. The most appropriate model for all shrubs included N‐dependent growth of linear rather than saturating form. Inclusion of plant–soil feedbacks better explained ring width and δ 15 N for eight of 10 individuals. Although N trajectories were individualistic, common mechanisms of varying strength confirmed the N‐dependency of shrub growth. The linear mechanism may reflect intense scavenging of scarce N; the importance of plant–soil feedbacks suggests that shrubs subvert the microbial bottleneck by actively controlling their environment. Abstract : See also the Commentary on this article by Street & Caldararu, 233 : 585–587 .